PENGAMBILAN KEPUTUSAN PENGHAPUSAN ASET BMN (BARANG MILIK NEGARA) BERUPA KDO (KENDARAAN DINAS OPERASIONAL) DENGAN KONDISI RUSAK (STUDI KASUS PADA SATUAN KERJA PELAKSANAAN JALAN NASIONAL METROPOLITAN I SURABAYA) - Jayanti, Rita Sri; Aryani Soemitro, Ria Asih; Suprayitno, Hitapriya (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
The research aims to formulate the government's assets disposal decision making and to determine its estimated value. The research type is descriptive analysis using primary data collected from direct observation in the field and secondary data sourced from Satuan Kerja Pelaksanaan Jalan Nasional Metropolitan I Surabaya. This research uses flowcharts, photo documentation, and asset valuation calculations using Depreciate Replacement Cost (DRC) method. The research object are five government vehicles. The results showed that from those five vehicles, three motorbikes and two cars that have various levels of damage, three motorbikes can be disposed and two cars can be repaired. The results of this study are expected to be used for planning the assets disposal and proposing the estimated value of the assets.